Servant Leadership Model: Studi Kasus pada Dinas Kependudukan Provinsi Jawa Timur - Agni Shanti Mayangsari; Wahyu Eko Pujianto (Public Administration Dept, Faculty of Social and Political Science, 2023)
This study aims to analyze and describe the servant leadership model that is applied in the work environment of the East Java Provincial Population Service. A qualitative case study design was chosen for this study. The reason for considering case studies is that servant leadership is a single concept to be explored as a process. Three types of qualitative data collection were carried out: in-depth interviews, open interviews, direct observation, and written documents. Based on the results described above, it can be concluded that the servant leadership that is applied to East Java dispenduk refers to the concept of Spears (2004) which adheres to 10 principles of leadership namely, 1) community building, (2) persuasion and (3) stewardship, (4) ) listening, (5) empathy, (6) healing, (7) awareness, (8) commitment to the growth of people, (9) foresight and (10) conceptualization. Servant leadership illustrates the belief that organizational goals will be achieved in the long term only by first facilitating the growth, development, and general well-being of the individuals who make up the organization. Therefore, servant leadership is a leadership style that must be embraced by today's organizations to increase employee loyalty, commitment, and performance.